THE ROLE OF GUAVA FRUIT FILTRATE ON MAINTAINING THE PRE-FREEZING AND POST-THAWED QUALITY OF BALI BULL SPERMATOZOA - I Wayan Lanus Sumadiasa; Lukman Lukman; Rodiah Rodiah (Jurnal Kedokteran Hewan, 2018)
This study aimed to determine the role of guava fruit filtrate (GFF) on maintaining the pre-freezing and post-thawed quality of Bali bullspermatozoa in tris-egg yolk (TEY) extender. The bovine semen was collected using artificial vagina twice a week (n= 10). Ejaculate sampleswere divided into four tubes and each tube was respectively added the following diluents: TEY, TEY + 5% GFF, TEY + 10% GFF, and TEY +15% GFF. The diluted semen was filled into the straws (0.25 mL) and cooled in refrigerator at 4° C for 2.5 hours. The samples were kept onvapor phase of liquid nitrogen (N2) (-120° C) for 10 minutes prior to be stored in liquid phase (-196° C). The quality of pre-freezing and postthawedspermatozoa in straw sample (i.e. motility, viability, and abnormality) was evaluated under light microscopy at 400x magnification. Datawere analysed statistically. The percentage of motility and viability both on pre-freezing and post-thawed process were significantly higher insemen diluted with TEY + 10% GFF compared to control (TEY), TEY + 5% GFF, and TEY + 15% GFF. Addition of 10% GFF into tris-egg yolkextender play role for maintaining the quality of pre-freezing and post-thawed Bali bull spermatozoa.